Assisted reproductive technologies and genetic improvement strategies for enhancing livestock production and food security in Tropical East Africa: A review - Bangert, E. A.; Wheeler, M. B. (Journal of Scientific Agriculture, 2025)
Despite an increase in global food availability, food insecurity remains a pressing global challenge affecting millions across developed and developing nations. This issue is particularly severe in developing countries in tropical regions, where harsh climatic conditions, low agricultural productivity, and limited access to resources intensify the challenge of food insecurity. Africa exemplifies these challenges, with approximately 20% of the total population undernourished. East Africa is no stranger to these statistics with 31.8% of the country’s children under 5 years old being malnourished. Many livestock production systems in tropical East Africa operate significantly below their potential due to constraints including climate vulnerability, endemic diseases, and low genetic production capacity of indigenous breeds. Improving livestock productivity has been an area of focus for improving food security for many years. Applying our knowledge of environmental adaptations such as heat tolerance mechanisms like the SLICK gene in cattle and fat tails in sheep and disease resistance traits like trypanotolerance is a foundational step in the development of breed improvement programs for the tropics. Crossbreeding programs have utilized this knowledge for decades resulting in great success stories such as the Girolando cattle of Brazil, which are responsible for producing 80% of the country’s milk today. With the development and use of assisted reproductive technologies (ARTs) like artificial insemination, in vitro fertilization & embryo transfer we have the ability to achieve genetic gain at an unprecedented speed. Many cases have demonstrated promising applications of these technologies, with one such study reporting IVF and ET implementation in Kenyan dairy herds could increase monetary gain by 184% while reducing generation intervals by 47%. Overall, strategic implementation of genetic improvement programs, when adapted to the diverse livestock production systems of the developing tropics hold the key to significantly enhancing livestock productivity, improving food security, and overall contributing to more sustainable agricultural systems in East Africa.